ANALISIS PENGARUH LINGKUNGAN KERJA, KUALITAS KEPEMIMPINAN, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Studi Pada PT. PLN (Persero) Kantor Distribusi Jateng dan D.I.Yogyakarta) - Ardiyani, Nurul Ana; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2017)
Employee performance decline at PT. PLN (Persero) Distribution Office of Central Java and DIY in the first semester of 2016. In addition there is a research gap on the relationship of work environment, leadership quality and work motivation on employee performanceThis study aims to determine the effect of work enviroment, quality leadership, and motivation work on employee performance at PT. PLN (Persero) Distribution Office of Central Java and DIY. The sample inthis study is employess of PT. PLN (Persero) Distribution Office Central Java and DIY that amounted to 74 people with using random sampling technique.Data tabulation in this study includes validity test, reliability test, clasiccal assumption test, multiple linier regression analysis, T test, F test, and coefficient of determination test. The result of this research shows that the independent variable that is work environment (0, 386) leadership quality (0.251) and work motivation (0.264) have positive and significant relation to dependent variable that is employee performance.